Varus will Have Varus; A Radiological Study to Assess and Predict Varus Stem Placement in Uncemented Femoral Stems. Issue 6 (10th November 2016) - Murphy, Colin G.; Bonnin, Michel P.; Desbiolles, Antoine H.; Carrillon, Yannick; Aїt Si Selmi, Tarik
Background: Varus inclination of the uncemented stem is not necessarily a technical error. The proximal femoral anatomy of hips with a coxa vara deformity frequently predisposes varus inclination. Methods: We reviewed a series of 200 patients undergoing primary uncemented THA with the Corail® hip system. Preoperative data were based on patient demographics, diagnosis, and radiographic information (preoperative templating-CT measurements), and compared postoperative alignment for each stem and type of stem used. Proximal femoral traits which can alert surgeons, when templating preoperatively, to potential varus alignment were noted. Results: All stems were inserted either in neutral or varus alignments. Low neck shaft angle is strongly predictive of increased varus stem alignment (p<0.001). Stems inserted with higher varus alignment were associated with the preoperative morphological traits associated with coxa vara hip deformities – increased femoral offset (p<0.001), greater trochanteric overhang (p<0.001), greater trochanteric height (p<0.046), and a lower canal flare index (p<0.046). Conclusions: Varus stem alignment is neither unexpected nor necessarily a technical failure when using this particular uncemented stem system. Coxa vara deformities, due to a combination of morphological traits, are more likely to be inserted with higher varus alignment than hips with normal or higher neck shaft angles. Surgeons need to be aware of this when carrying out preoperative templating and intraoperative assessment, in order to prevent over-compensation for offset, length or stability.